Vulnerabilidades em saúde da população LGBTQI+: Existências fora do armário - Silva, Ricard Jose Bezerra da (2021)
This dissertation had as general objective to analyze the health vulnerabilities of LGBTQIA+ in its historical aspects, public policies and in relation to sexual and preventive practices and access to health services. Therefore, two studies were carried out, which were structured in two articles. The first study aimed to analyze the historical course of Brazilian legislation in relation to the guarantee of rights and public policies aimed at the LGBTQIA+ population. It was an exploratory, descriptive research, based on the documentary research method and with a qualitative approach. 37 official documents that brought contributions and/or interference to the processes of accessing and structuring the health of the LGBTQIA+ population were analyzed. The documents were categorized through Thematic Categorical Analysis, which allowed the grouping of contents into four categories: (a) Social name and recognition of gender identity, (b) Combating discrimination against LGBTQIA+ people and professional practices; (c) Access to health services; and (d) Fostering the representation of LGBTQIA+ people in the political sphere of the SUS. The little production of laws that guarantee access to and mitigation of discrimination processes for the LGBTQIA+ population was evidenced. In turn, the second study aimed to analyze the health vulnerabilities of the LGBTQAI+ population in relation to sexual and preventive practices and access to health services. Participated, in a non-probabilistic way and for convenience, 562 people with ages ranging from 18 to 65 years old (M=27 years old; SD=6.93). A sociodemographic questionnaire and a questionnaire on access to and satisfaction with public health services and on sexual and preventive practices were used as instruments. Data were analyzed using descriptive statistics. The results showed that only 29.4% of the participants declared to know the National Policy for Comprehensive Health for the LGBT Population. As for access, 57.3% of the total sample claimed to seek services only when needed. For most participants (69.4%), no Community Health Agent monitors their residence. Furthermore, 46.1% of the participants believe that public health services are not prepared to receive them. Among the main difficulties in going to the public health service, the participants highlighted the neglect of the public health service, prejudice and access. However, most of the participants stated that they were satisfied with the health services both in the neighborhood and in the city where they live. It is concluded that the LGBTQIA+ population does not effectively access public health services, which is related to individual, social and programmatic vulnerabilities. Identifying the aspects that limit and/or hinder the access of LGBSTQIA+ people to public health services remains a challenge.